Construction method of cathode-free solid sodium battery interface
By constructing a three-dimensional porous skeleton in a negative electrode-free solid-state sodium battery and coating it with sodium biphenyl solution, the problem of poor interface stability between the solid electrolyte and the current collector was solved, and the long-cycle stability and high safety of the battery were achieved.
Patent Information
- Application Number
- CN202510715667.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-09-26
AI Technical Summary
In anode-free solid-state sodium batteries, the interface stability between the solid electrolyte and the current collector is poor, resulting in a shortened cycle life, and volume fluctuations during the deposition of metallic sodium lead to interface failure.
A three-dimensional porous skeleton was constructed and coated with sodium biphenyl solution to form a quasi-liquid interface layer, which regulated the electric field distribution, inhibited dendrite formation, and promoted uniform sodium deposition.
It improves the cycle stability and electrochemical performance of the battery, extends the battery life, reduces the nucleation potential of sodium deposition, and reduces the occurrence of side reactions.
Smart Images

Figure CN120709513A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a method for constructing an interface of a negative-electrode-free solid-state sodium battery. Background Art
[0002] Secondary battery systems, represented by lithium-ion batteries, have been widely used in consumer electronics, drones, and new energy vehicles due to their advantages such as high energy density and long cycle life, and continue to promote innovation in energy storage technology. However, due to the limited reserves of lithium resources, the price of lithium-ion batteries has also risen rapidly with the growth of market demand, and low-cost alternative materials are needed. Sodium and lithium belong to the same group of elements and have a higher theoretical energy density (1166 mAh g −1 ) and a lower redox potential (-2.71 V vs SHE), and the natural abundance of sodium is 1000 times higher than that of lithium, making sodium batteries a cost-competitive alternative to lithium batteries. However, traditional liquid sodium battery systems have safety risks such as flammable and leaky electrolytes, making it difficult for the battery cycle life and safety to meet commercial requirements. In contrast, solid-state sodium-ion batteries, due to their excellent safety and stability, can achieve energy densities comparable to lithium-ion batteries. Anode-free batteries are an emerging battery structure design. Unlike traditional batteries, the anode-free battery initially has no active material and does not rely on carbon-based or alloy anodes to store ions. Instead, during charging, alkali metals are directly deposited on the current collector surface through in situ electrochemical methods. Therefore, they have high energy density and high safety. Anode-free solid-state sodium-ion batteries use solid electrolytes instead of conventional liquid electrolytes, fundamentally eliminating the risk of electrolyte decomposition and improving battery safety.
[0003] Anode-free solid-state sodium batteries face significant challenges in terms of cycling stability. This is primarily due to the solid-solid point contact between the solid electrolyte and the current collector. This, coupled with the large volume fluctuations during the deposition and dissolution of metallic sodium, further accelerates interfacial failure, thereby shortening the overall battery cycle life. To address this issue, rationally constructing a fast charge transfer interface between the solid electrolyte and the current collector can achieve multiple optimization effects, effectively improving the electrochemical performance of anode-free solid-state sodium-ion batteries. Summary of the Invention
[0004] In order to solve the above technical problems, the present invention provides a method for constructing a negative electrode-free solid-state sodium battery interface, which can effectively improve the interface stability between the current collector and the electrolyte, adjust the electric field distribution, reduce the nucleation potential of sodium, inhibit dendrite formation, promote uniform sodium deposition, and improve the cycle stability of the battery.
[0005] To achieve this technical purpose, the present invention adopts the following scheme: The present invention provides a method for constructing a negative electrode-free solid-state sodium battery interface, comprising the following steps: S1. Construction of a three-dimensional porous skeleton: A pore-forming agent is added to the solid electrolyte precursor powder and mixed uniformly. An organic carrier is then added and ball-milled to form a slurry. The slurry is evenly coated on one side of the solid electrolyte using screen printing technology. After calcination, the pore-forming agent and organic carrier are removed to obtain a three-dimensional porous framework with a certain strength. S2. Preparation of sodium biphenyl solution: Weigh biphenyl and sodium in proportion, add them to an organic solvent, and obtain a sodium biphenyl solution after complete dissolution. The concentration is controlled to be 0.1-5 M. S3. Dropping the sodium biphenyl solution prepared in step S2 onto the three-dimensional porous skeleton prepared in step S1 to obtain a stable quasi-liquid interface layer; placing the solid electrolyte containing the quasi-liquid interface layer between the positive electrode and the negative electrode current collector of the sodium ion battery to prepare a negative electrode-free solid-state sodium battery.
[0006] Compared with the prior art, the present invention has the following beneficial effects: By constructing a quasi-liquid sodium biphenyl interface supported by a three-dimensional porous framework, this invention effectively alleviates the localized polarization caused by the contact between the solid electrolyte and the current collector, enabling rapid and uniform interfacial charge transfer. This artificial sodium biphenyl interface layer can regulate the electric field distribution, reduce localized excessive electric field strength, lower the nucleation barrier for sodium deposition, and inhibit the growth of metallic sodium dendrites. Anode-free sodium batteries modified with this artificial interface layer exhibit long-term cycle stability and excellent performance.
[0007] Furthermore, the solid electrolyte in step S1 is NASCION type Na 3.2 Zr2Si 2.2 PO 12 , β′′-Al2O3, sodium yttrium silicate (NYS) or at least one or more thereof.
[0008] Furthermore, in step S1, the pore-forming agents are starch and carbon nanotubes, and the mass ratio of starch to carbon nanotubes is 1-9:1-9.
[0009] Furthermore, in step S1, the organic carrier is ethyl cellulose and butyral, and the mass ratio of ethyl cellulose to butyral is 1-9:1-9.
[0010] Furthermore, in step S1, the mass ratio of the precursor to the organic carrier is 1-9:1-9.
[0011] Furthermore, the ball milling time in step S1 is 8 to 24 hours; the calcination temperature is 900 to 1150 o C, calcination time is not less than 3 hours.
[0012] Furthermore, step S2 is performed in a glove box, the sodium used to prepare the biphenyl solution has completely removed the oxide layer, and the mass ratio of biphenyl to sodium is 0.5~2:0.5~2.
[0013] Furthermore, the organic solvent in step S2 is one or more of ethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, ethylene carbonate, and dimethyl carbonate.
[0014] Furthermore, the cathode active material of the negative electrode-free solid-state sodium battery adopts one of sodium vanadium phosphate, sodium nickel iron manganese oxide, Prussian blue or other sodium-containing cathode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The cycle capacity retention rate of the negative electrode-free solid-state sodium battery containing an interface prepared in Example 1 and Comparative Example 2.
[0016] Figure 2 Sodium ion nucleation overpotential curves of the negative electrode-free solid-state sodium battery containing an interface prepared in Example 1 and Comparative Example 2.
[0017] Figure 3 This is the impedance test curve of sodium biphenyl solution with different concentrations. DETAILED DESCRIPTION
[0018] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments, but the present invention is not limited thereto.
[0019] First of all, it should be noted that, unless otherwise specified, all the drugs used in this application are commercially available drugs.
[0020] The present invention provides a method for constructing a negative electrode-free solid-state sodium battery interface, comprising the following steps: S1. Construction of a three-dimensional porous skeleton: A pore-forming agent is added to the solid electrolyte precursor powder and mixed uniformly. An organic carrier is then added and ball-milled to form a slurry. The slurry is evenly coated on one side of the solid electrolyte using screen printing technology. After calcination, the pore-forming agent and organic carrier are removed to obtain a three-dimensional porous framework with a certain strength. Among them, the solid electrolyte is NASCION type Na 3.2 Zr2Si 2.2 PO 12 At least one or more of (NZSP), β′′-Al2O3, and sodium yttrium silicate (NYS); The pore-forming agents are starch and carbon nanotubes, and the mass ratio of starch to carbon nanotubes is 1~9:1~9; The mass ratio of precursor powder to pore-forming agent is 6~8:4~2; The organic carrier is composed of ethyl cellulose and butanol, and the mass ratio of the two is 1~9:1~9; The mass ratio of precursor to organic carrier is 1~9:1~9; The ball milling time is 8~24 hours, and the calcination temperature is 900~1150 o C, calcination time is not less than 3 hours.
[0021] S2. Preparation of sodium biphenyl solution: In a glove box, weigh appropriate amounts of biphenyl and sodium, with the oxide layer of sodium completely removed, at a mass ratio of 0.5-2:0.5-2. Add them to an organic solvent and wait for complete dissolution to form a sodium biphenyl solution with a concentration of 0.1-5 M. The organic solvent is one or more of ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF), 1,3-dioxolane (DOL), ethylene carbonate (EC), and dimethyl carbonate (DEC); S3. Dropping the sodium biphenyl solution prepared in step S2 onto the three-dimensional porous skeleton prepared in step S1 to obtain a stable quasi-liquid interface layer.
[0022] The prepared artificial interface layer is applied to a negative electrode-free solid-state sodium battery. The negative electrode side current collector is a copper foil (diameter 10 mm), and the electrolyte sheet adopts a solid electrolyte sheet with an interface layer, and the interface layer is used on the negative electrode side.
[0023] The positive electrode sheet was prepared according to the conventional method: the positive electrode active material, conductive carbon black (Super P) and binder polyvinylidene fluoride (PVDF) were mixed in a ratio of 8:1:1 and ground thoroughly in a mortar to ensure its uniformity. Then, an appropriate amount of N-methylpyrrolidone (NMP) was added as a solvent and further ground to form a black slurry. Next, the aluminum foil was cut into appropriate sizes and the slurry was evenly coated on the aluminum foil. Subsequently, the coated aluminum foil was placed in a vacuum oven at 120 o C for more than 10 hours to make it fully dry. The area mass loading of the active material on the positive electrode is 2~15 mg·cm -2 Finally, the dried material was cut into discs with a diameter of 10 mm and used as positive electrode sheets. Example 1
[0024] This embodiment provides a method for constructing an interface of a negative electrode-free solid-state sodium battery, and the specific steps are as follows: S1. Construction of a three-dimensional porous framework Na 3.2 Zr2Si 2.2 PO 12Preparation of (NZSP) solid electrolyte: Weigh the dried drugs, ball mill them and mix them evenly, then heat them at 900 o Calcinate at 1250 °C for 12 hours. Grind the sintered electrolyte and add 1 wt% polyvinyl butyral and continue ball milling for 24 hours before drying. Press into tablets using a tablet press and cold isostatic press. o C for 16 hours to obtain Na 3.2 Zr2Si 2.2 PO 12 Solid electrolyte sheet.
[0025] To unsintered Na 3.2 Zr2Si 2.2 PO 12 A pore-forming agent (NZSP powder and pore-forming agent mass ratio of 7:3; the pore-forming agent is a mixture of starch and carbon tubes at a mass ratio of 1:1) is added to the (NZSP) precursor powder, mixed evenly, and then placed in a ball mill for 10 hours. Then, an organic carrier (the organic carrier is a mixture of ethyl cellulose and butanol at a mass ratio of 1:1) is added at a mixture / organic carrier mass ratio of 3:7. Ball milling is performed at room temperature for 12 hours to form a slurry, and the mixed slurry is coated on one side of the solid electrolyte sheet (NZSP) by screen printing. At 1150 o After calcination at 400 °C for 5 hours to remove the pore-forming agent and the organic carrier, a porous electrolyte layer with a certain strength was obtained.
[0026] S2. Preparation of sodium biphenyl solution In a glove box, 0.7705 g of biphenyl and 0.115 g of sodium were weighed and fully dissolved in ethylene glycol dimethyl ether (DME) to obtain a 5 M sodium biphenyl solution.
[0027] S3, 20 μL of the sodium biphenyl solution prepared in step S2 was added dropwise to the porous framework prepared in step S1 to obtain a Na 3.2 Zr2Si 2.2 PO 12 electrolytes.
[0028] The positive electrode material is sodium vanadium phosphate. Sodium vanadium phosphate, conductive carbon black (Super P) and binder polyvinylidene fluoride (PVDF) are mixed in a ratio of 8:1:1 and fully ground in a mortar to ensure its uniformity. Then, an appropriate amount of N-methylpyrrolidone (NMP) is added as a solvent and further ground to form a black slurry. Next, the aluminum foil is cut into appropriate sizes and the slurry is evenly coated on the aluminum foil. Subsequently, the coated aluminum foil is placed in a vacuum oven at 120 o C for more than 10 hours to make it fully dry. The area mass loading of the active material on the positive electrode is 2.5 mg cm-2 Finally, the dried material was cut into discs with a diameter of 10 mm and used as positive electrode sheets.
[0029] Full-cell assembly and testing: Assembly was performed in an argon-protected glove box. A sodium vanadium phosphate cathode sheet (10 mm diameter) was used as the positive electrode, a copper foil (10 mm diameter) as the current collector on the negative electrode, and the electrolyte sheet prepared above, which has a quasi-liquid interface. To ensure contact between the positive electrode and the solid electrolyte, 15 μL of 1 M NaPF₆ electrolyte (DEC:DMC:EC = 1:1:1 vol%) with 5% FEC was added to the positive electrode. The assembled full-cell was first allowed to rest at room temperature for 1 hour before charge-discharge testing was performed at a voltage range of 2–3.8 V and a rate of 1C. The capacity retention was recorded after 200 cycles.
[0030] Assembly and testing of the Na|NZSP|Cu half-cell: Assembly was performed in an argon-protected glove box. Copper foil was used as the positive electrode, and a sodium sheet (10 mm in diameter) was used as the negative electrode. 15 μL of 1M NaPF6 electrolyte (DEC:DMC:EC = 1:1:1 Vol% with 5% FEC) was added to the Na|NZSP side. After the assembled half-cell was allowed to stand for 1 hour, its nucleation overpotential was measured. At 0.1 mA·cm -2 The cell was discharged at a current density of 2 h and the nucleation overpotential was recorded.
[0031] Solution impedance test: The impedance test of the prepared sodium biphenyl solution was carried out using a conductivity electrode composed of parallel platinum-carbon electrode sheets. Example 2
[0032] Step S3, battery assembly and testing methods of this embodiment are the same as those of embodiment 1, with the following differences from embodiment 1: S1. Prepare solid electrolyte sodium yttrium silicate (NYS) by high temperature solid phase method: weigh the dried drugs, ball mill them and mix them evenly, then heat them at 950 o Calcinate at 1050 °C for 8 hours. Grind the sintered electrolyte and add 1 wt% polyvinyl butyral and continue ball milling for 24 hours before drying. Press into tablets using a tablet press and cold isostatic press. o C for 36 hours to obtain Na5YSi4O 12 Solid electrolyte sheet.
[0033] Add pore-forming agent to the NYS precursor powder that has not been sintered into an electrolyte sheet (the mass ratio of NYS precursor powder to pore-forming agent is 7:3; the pore-forming agent is a mixture of starch and carbon tubes in a mass ratio of 1:1), mix them evenly, and place them in a ball mill for 10 hours. Then, add an organic carrier (the organic carrier is a mixture of ethyl cellulose and butanol in a mass ratio of 1:1) at a mixture / organic carrier mass ratio of 3:7. Ball mill at room temperature for 20 hours to form a slurry, and use screen printing to apply the mixed slurry to one side of the solid electrolyte. At 950 o After calcination at 400 °C for 5 hours to remove the pore-forming agent and the organic carrier, a porous electrolyte layer with a certain strength was obtained.
[0034] S2. In a glove box, weigh 0.3084 g of biphenyl and 0.046 g of sodium, and dissolve them in DME to obtain a 2 M sodium biphenyl solution. Example 3
[0035] Step S3, battery assembly and testing methods of this embodiment are the same as those of embodiment 1, with the following differences from embodiment 1: S1. Prepare β′′-Al2O3 solid electrolyte by high temperature solid phase method. Weigh the dried drugs, ball mill them and mix them evenly. Then calcine them at 1250℃ for 2 hours. Grind the sintered electrolyte, add 1 wt% polyvinyl butyral and continue ball milling for 24 hours. Then dry it. Press it into tablets using tablet press and cold isostatic press. The electrolyte tablets are first heated at 650℃. o C for 2 hours, and then heated to 1580 ° C for 3 hours to obtain a β''-Al2O3 solid electrolyte sheet.
[0036] The β′′-Al2O3 precursor powder that has not been sintered into an electrolyte sheet is added with a pore-forming agent (the mass ratio of the precursor powder to the pore-forming agent is 7:3; the pore-forming agent is a mixture of starch and carbon tubes in a mass ratio of 1:1), mixed evenly, and then placed in a ball mill for 10 hours. Then, an organic carrier is added at a mixture / organic carrier mass ratio of 3:7 (the organic carrier is a mixture of ethyl cellulose and butanol in a mass ratio of 1:1). Ball milling is performed at room temperature for 10 hours to form a slurry, and the mixed slurry is coated on one side of the solid electrolyte by screen printing. At 1400 o After calcination at 400 °C for 5 hours to remove the pore-forming agent and the organic carrier, a porous electrolyte layer with a certain strength was obtained.
[0037] S2. In a glove box, weigh 0.1541 g of biphenyl and 0.023 g of sodium, and dissolve them in DME to obtain a 1 M sodium biphenyl solution. Example 4
[0038] The differences between this embodiment and embodiment 1 are as follows: The organic solvent in step S2 is tetrahydrofuran (THF). Example 5
[0039] The differences between this embodiment and embodiment 1 are as follows: The calcination temperature in step S1 is 1000 o C.
[0040] The organic solvent in step S2 is 1,3-dioxolane (DOL). Example 6
[0041] The differences between this embodiment and embodiment 1 are as follows: S2. In a glove box, weigh 0.077 g of biphenyl and 0.0115 g of sodium, and dissolve them in ethylene carbonate (EC) to obtain a 0.5 M sodium biphenyl solution. Example 7
[0042] S2. In a glove box, weigh 0.0308 g of biphenyl and 0.0046 g of sodium, and dissolve them in dimethyl carbonate (DEC) to obtain a 0.2 M sodium biphenyl solution.
[0043] Comparative Example 1 The difference from Example 1 is that the solid electrolyte uses an NZSP electrolyte sheet without porous modification and without an interface layer. The unmodified battery short-circuits due to dendrite growth and cannot cycle normally.
[0044] Comparative Example 2 The difference from Example 1 is that 1M NaPF6 electrolyte was dripped onto the three-dimensional porous skeleton, the solvent was DEC:DMC:EC=1:1:1 Vol% with 5% FEC, the obtained solid electrolyte sheet was assembled into a battery according to the method of Example 1, and the test was carried out according to the method of Example 1.
[0045] The impedance test curves of sodium biphenyl solutions with different concentrations are as follows: Figure 3 The conductivity of sodium biphenyl solutions of different concentrations in each embodiment is calculated and shown in Table 1. It can be seen that as the concentration of sodium biphenyl increases, the conductivity of the solution also increases. The sodium biphenyl solution with high conductivity can fully meet the ion transport at the interface.
[0046] Table 1 Conductivity of sodium biphenyl solutions with different concentrations Concentration / M <![CDATA[Conductivity / S·cm -1 > Example 1 5 <![CDATA[1.75×10 -2 <!-- 5 -->]]> Example 2 2 <![CDATA[1.4×10 -2 ]]> Example 3 1 <![CDATA[1.2×10 -2 ]]> Example 6 0.5 <![CDATA[6.1×10 -3 ]]> Example 7 0.2 <![CDATA[1.6×10 -3 ]]> The test results of Example 1 and Comparative Example 2 are as follows: Figure 1 and Figure 2 See Figure 1The initial capacity of the full battery in Example 1 is not much different from that in Comparative Example 2. The full battery in Comparative Example 2 begins to show obvious capacity decay after nearly 20 cycles. In contrast, the full battery in Example 1 can be cycled for 200 cycles without significant capacity decay, and the capacity retention rate reaches more than 95%. Figure 2 In the nucleation overpotential test, the nucleation overpotential in Example 1 was 10 mV, and the nucleation potential in Comparative Example 2 was 30 mV. The results show that compared with Comparative Example 2, the interface layer has a stronger affinity for sodium and is easier to nucleate during the deposition process. The interface layer fills the gap between the current collector and the solid electrolyte, increasing the contact area. The high ionic conductivity of the interface layer regulates the electric field distribution, and the uniform electric field distribution reduces the local excessive electric field strength and reduces the nucleation potential of sodium deposition. It promotes uniform sodium deposition, prevents dendrite formation, and reduces the risk of battery failure. Uniform contact and lower nucleation potential reduce the occurrence of side reactions and improve the cycle stability of the battery.
[0047] Finally, it should be noted that the above-listed embodiments are merely preferred embodiments of the present invention. Of course, those skilled in the art may make changes and modifications to the present invention. If these modifications and variations fall within the scope of the claims of the present invention and their equivalents, they should be considered to be within the scope of protection of the present invention.
Claims
1. A method for constructing a negative electrode-free solid-state sodium battery interface, characterized in that: The following steps are involved: S1. Construction of a three-dimensional porous skeleton: A pore-forming agent is added to the precursor powder of the solid electrolyte and mixed uniformly. An organic carrier is then added and ball-milled to form a slurry. The slurry is evenly coated on one side of the solid electrolyte using screen printing technology. After calcination, the pore-forming agent and organic carrier are removed to obtain a three-dimensional porous framework with a certain strength. S2. Preparation of sodium biphenyl solution: Weigh biphenyl and sodium in proportion, add them to an organic solvent, and obtain a sodium biphenyl solution after complete dissolution. The concentration is controlled to be 0.1-5 M. S3. Dropping the sodium biphenyl solution prepared in step S2 onto the three-dimensional porous skeleton prepared in step S1 to obtain a stable quasi-liquid interface layer; placing the solid electrolyte containing the quasi-liquid interface layer between the positive electrode and the negative electrode current collector of the sodium ion battery to prepare a negative electrode-free solid-state sodium battery.
2. The method for constructing a negative electrode-free solid-state sodium battery interface according to claim 1, characterized in that: The solid electrolyte in step S1 is Na NASCION type 3.2 Zr2Si 2.2 PO 12 , β′′-Al2O3, and at least one or more of sodium yttrium silicate.
3. The method for constructing a negative electrode-free solid-state sodium battery interface according to claim 1, characterized in that: In step S1, the pore-forming agents are starch and carbon nanotubes, and the mass ratio of starch to carbon nanotubes is 1-9:1-9.
4. The method for constructing a negative electrode-free solid-state sodium battery interface according to claim 1, characterized in that: In step S1, the organic carrier is ethyl cellulose and butanol, and the mass ratio of ethyl cellulose to butanol is 1-9:1-9.
5. The method for constructing a negative electrode-free solid-state sodium battery interface according to claim 1, characterized in that: In step S1, the mass ratio of the precursor to the organic carrier is 1-9:1-9.
6. The method for constructing a negative electrode-free solid-state sodium battery interface according to claim 1, characterized in that: The ball milling time in step S1 is 8 to 24 hours; the calcination temperature is 900 to 1150 o C, calcination time is not less than 3 hours.
7. The method for constructing a negative electrode-free solid-state sodium battery interface according to claim 1, characterized in that: Step S2 is performed in a glove box. The metallic sodium used to prepare the sodium biphenyl solution has had its oxide layer completely removed, and the mass ratio of biphenyl to sodium is 0.5-2:0.5-2.
8. The method for constructing a negative electrode-free solid-state sodium battery interface according to claim 1, characterized in that: The organic solvent in step S2 is one or more of ethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, ethylene carbonate, and dimethyl carbonate.
9. The method for constructing a negative electrode-free solid-state sodium battery interface according to claim 1, characterized in that: The cathode material of the negative electrode-free solid-state sodium battery is one of sodium vanadium phosphate, sodium nickel iron manganese oxide, Prussian blue or other sodium-containing cathode materials.
Citation Information
Cited By
Alloy negative electrode composite sodium solid electrolyte material and preparation method and application thereof
CN121662930A
Alloy negative electrode composite sodium solid electrolyte material, preparation method and application thereof
CN121662930B